Možnosti subpixelového přístupu pro klasifikaci vegetace z hyperspektrálních a multispektrálních dat v krkonošské tundře - Růžička, Josef (Univerzita Karlova, Přírodovědecká fakulta, 2022)
This diploma thesis focuses on the possibilities and potential of using subpixel-based classification methods for hyperspectral and multispectral data capturing selected localities of the tundra in the Krkonoše Mountains, specifically the Bílá louka meadow and Luční hora mountain areas. The thesis presents current methods for collecting and using endmembers as well as methods for the classification itself using the spectral unmixing approach, mainly in connection with the classification of heterogeneous vegetation communities. In the practical part of the thesis, various methods of collecting end members are used, especially the extraction of end member spectra directly from image data using manual, semi-automatic and automatic methods. Envi, EnMAP-Box 3 and MATLAB software are used for collection and subsequent classification. Endmembers collected in different ways are then combined with different classification methods in an attempt to achieve the most accurate result possible, which would be at the level of controlled pixel-based classification. The classification took place on two legend levels. Detailed, classifying individual plant species and less detailed, where species are aggregated into larger groups. The best results were achieved by the classification of the Bílá louka meadow. Tato diplomová práce se zaměřuje na možnosti a potenciál využití metod subpixelové klasifikace pro hyperspektrální a multispektrální data zachycující vybrané lokality Krnonošské tundry, konkrétně oblasti Bílé louky a Luční hory. V rámci práce jsou představeny současné metody pro sběr a využití koncových členů i metody k samotné klasifikaci s využitím přístupu spektrálního unmixingu, hlavně pak v souvislosti s klasifikací heterogenních vegetačních společenstev. V praktické části práce jsou pak využity různé metody sběru koncových členů, především pak extrakce spekter koncových členů přímo z obrazových dat pomocí manuální, poloautomatické a automatické metody. Ke sběru i následné klasifikaci jsou využívány softwary Envi, ...